Employee Engagement and Corporate Sustainable Practices: Insights from Selected F&B Manufacturing Industry Employees - Gonzales, John Christian; Renomeron, Carla Jiselle; Perono, Irvin; Jimenez, Princess Khayle (Journal of Social Entrepreneurship Theory and Practice, 2025)
Corporate sustainability is increasingly becoming a strategic priority in the food and beverage (F&B) industry, where businesses are under growing pressure to integrate responsible practices without compromising profitability. This study examines the relationship between corporate sustainability practices and employee engagement in Metro Manila's F&B sector. Specifically, this study’s objective aims to assess how sustainability initiatives influence the development of a sustainable culture by analyzing their impact on long-term company growth, organizational procedures, and employee personal behaviors. The research tests the hypothesis: Ho: There is no significant relationship between employee engagement and corporate sustainability practices. Using simple random sampling, data were collected from 385 employees across the industry. Employee engagement was assessed through six dimensions: quality of life, work, people, opportunities, rewards, and company practices. Sustainability practices were categorized into environmental, economic, and social pillars. Descriptive statistics were used to summarize findings, while Spearman’s Rank correlation determined the strength of the relationship. Results revealed high levels of both employee engagement and corporate sustainability practices. A significant moderate positive correlation was found, rejecting the null hypothesis and confirming that sustainability practices are meaningfully linked to employee engagement. These insights underscore the importance of embedding sustainability in business strategies, not only for environmental and social impact but also for enhancing employee motivation and retention. The study provides HR practitioners and decision-makers with a basis for developing targeted programs that align sustainability with workforce engagement, ultimately supporting sustainable growth in the F&B sector.